1996
DOI: 10.1139/b96-120
|View full text |Cite
|
Sign up to set email alerts
|

Changes in levels of foliar carbohydrates and myo-inositol before premature leaf senescence of Populus nigra induced by a mixture of O3 and SO2

Abstract: Specimens of Populus nigra L. cv. Loenen exhibit premature leaf senescence when exposed for a few weeks to realistic air pollution. In this study, the changes in levels of foliar carbohydrates and myo-inositol (MI) due to 30 ± 1 nL/L O3 + 12 ± 1 nL/L SO2 from the onset of exposure to the occurrence of premature abscission is presented. Petioles and laminae of the 12 oldest leaves were separately analysed on days 0, 4, 8, 12, 16, 20, 22, and 32 of continuous exposure, which was performed in open-top chambers (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…The effects of O 3 on foliar nonstructural carbohydrate concentrations were complicated. For example, the concentrations of non-structural carbohydrates in the leaves were found to be reduced by exposure to O 3 in Populus nigra, Picea abies and Pinus taeda (Meier et al 1990; Barnes et al 1995;Fialho and Bücker 1996), whereas the carbohydrate concentrations were increased or not affected by O 3 in Populus × euramericana, Pinus sylvestris and P. abies (Landolt et al 1994;Holopainen et al 1996;Utriainen and Holopainen 2000). In our previous studies, it was reported that net photosynthetic rate, starch grain size in chloroplasts and whole-plant dry mass of F. crenata seedlings were reduced by the exposure to O 3 (Yonekura et al 2001a, b).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of O 3 on foliar nonstructural carbohydrate concentrations were complicated. For example, the concentrations of non-structural carbohydrates in the leaves were found to be reduced by exposure to O 3 in Populus nigra, Picea abies and Pinus taeda (Meier et al 1990; Barnes et al 1995;Fialho and Bücker 1996), whereas the carbohydrate concentrations were increased or not affected by O 3 in Populus × euramericana, Pinus sylvestris and P. abies (Landolt et al 1994;Holopainen et al 1996;Utriainen and Holopainen 2000). In our previous studies, it was reported that net photosynthetic rate, starch grain size in chloroplasts and whole-plant dry mass of F. crenata seedlings were reduced by the exposure to O 3 (Yonekura et al 2001a, b).…”
Section: Discussionmentioning
confidence: 99%
“…RFO accumulation has been correlated with enhanced cold, heat and/or desiccation tolerance from algae to angiosperms ( Santarius 1973; Salerno and Pontis 1989; Hinesley et al 1992; Ashworth et al 1993; Wiemken and Ineichen 1993; Bachmann et al 1994). Additionally, RFOs correlate positively with needle longevity as well as ozone‐ and sulfide‐stress tolerance in conifers ( Mitcham‐Butler et al 1986; Fialho and Bücker 1996).…”
Section: Introductionmentioning
confidence: 99%
“…So far, it has been reported that they are involved in raYnose oligosaccharide metabolism (Gao and SchaVer 1999;Smart and Pharr 1980), stress tolerance in plants (Pennycooke et al 2003;Taji et al 2002) as well as galactolipid degradation during plant senescence (Fialho and Bücher 1995;Thompson et al 1998).…”
mentioning
confidence: 99%